Polyploids broadly generate novel haplotypes from trans-specific variation in Arabidopsis arenosa and Arabidopsis lyrata - Bohutínská, Magdalena; Petříková, Eliška; Booker, Tom R; Vives Cobo, Cristina; Vlček, Jakub; Šrámková, Gabriela; Poupětová, Alžběta; Hojka, Jakub; Marhold, Karol; Yant, Levi; Kolář, Filip; Schmickl, Roswitha (PLoS genetics, 2024)
Polyploidy, the result of whole genome duplication (WGD), is widespread across the tree of life and is often associated with speciation and adaptability. It is thought that adaptation in autopolyploids (within-species polyploids) may be facilitated by increased access to genetic variation. This variation may be sourced from gene flow with sister diploids and new access to other tetraploid lineages, as well as from increased mutational targets provided by doubled DNA content. Here, we deconstruct in detail the origins of haplotypes displaying the strongest selection signals in established, successful autopolyploids, Arabidopsis lyrata and Arabidopsis arenosa. We see strong signatures of selection in 17 genes implied in meiosis, cell cycle, and transcription across all four autotetraploid lineages present in our expanded sampling of 983 sequenced genomes. Most prominent in our results is the finding that the tetraploid-characteristic haplotypes with the most robust signals of selection were completely absent in all diploid sisters. In contrast, the fine-scaled variant 'mosaics' in the tetraploids originated from highly diverse evolutionary sources. These include widespread novel reassortments of trans-specific polymorphism from diploids, new mutations, and tetraploid-specific inter-species hybridization-a pattern that is in line with the broad-scale acquisition and reshuffling of potentially adaptive variation in tetraploids.
Keywords: tetraploidie; Tetraploidy; Meiosis; molekulární evoluce; genetická variace; meióza; Genetic Variation; Evolution, Molecular; Arabidopsis; diploidie; haplotypy; Genome, Plant; Haplotypes; Polyploidy; Selection, Genetic; polyploidie; selekce (genetika); Diploidy; genom rostlinný